Legal Analysis Number 1667/Pid.B/2024/Pn Lbp Concerning Robbery Resulting in Death - Philbert, Charles; Sijabat, Daniel Hefen; Hartono, Rudy (jurnal.unprimdn.ac.id, 2025)
Laws and regulations in Indonesia play an important role in maintaining public order and security. The legal system in this country is designed to regulate various aspects of life, including the prevention and handling of crime. Laws, such as the Criminal Code (KUHP) and other related regulations, aim to uphold justice and protect human rights. These provisions aim to provide a deterrent effect and combat the crime of mugging, as well as to protect the community to the maximum. This research is categorized as normative legal research, which focuses on the analysis of legal norms and applicable legal provisions. Based on the definition put forward by Soerjono Soekanto (2013), normative legal research examines how law as a written norm is applied in various concrete cases. This method is often used to understand and explain the application of law in certain situations by analyzing legal texts such as laws, regulations, and court decisions. In the context of this research, this approach is applied to examine legal norms related to mugging crime cases, especially through the analysis of regulations in the Criminal Code (KUHP).